Risk Perception of Traffic Participants - Arianne de Blaeij; Daniel van Vuuren (Tinbergen Institute, 2001)
In this paper we study the risk perception of traffic participants. Firstly, we give an overviewof previously used methodologies for the monetary valuation of transport safety. Thesemethodologies do not distinguish between the individual's assessment of probabilities and hervaluation of possible outcomes. A great disadvantage of these approaches is therefore that onehas to make the assumption that people correctly perceive the probabilities. Prospect theorydoes not make this assumption. Our procedure, which is based on this methodology, consistsof three steps. The first step is to determine the certainty equivalent for avoiding roadaccidents. The second step is the elicitation of the utility function. The final step is theelicitation of the probability weighting function. With this information we directly obtain theperceived value of the probability for accident Ai.The first, tentative, results show that the valuation of losses is wellrepresented by a utility function that is concave in shape. Secondly, ourpreliminary results show that when people have to choose whether or not toparticipate in a potentially risky activity with a low probability of the badoutcome (say ? 1/100), they base their decision on the possible outcomes ofthe activity rather than on the probabilities involved. The empiricalconclusion is therefore that people base their final decision mainly on thepossible outcomes and not so much on probabilities whenever there are verysmall probabilities involved.
Keywords: 330; Verkehrssicherheit; Risiko; Theorie